Factors contributing to customer satisfaction toward claim services in Anika Insurance Brokers Sdn Bhd / Mohd Amri Yusof Lateb - Yusof Lateb, Mohd Amri (Faculty of Business and Management, 2011)
The research entitled “Factors Contributing to Customer Satisfaction toward Claim Services in Anika Insurance Brokers Sdn Bhd” is conducted with four objectives mainly which the first objective is to measure the level of customer satisfaction towards claim services provided by Anika Insurance Brokers, second is to identify the most important factors that contributes to customer satisfaction toward claim services provided by Anika Insurance Brokers, third is to determine the direction of relationship between Service Quality and Commitment toward Customer Satisfaction and the last objective is to determine the direction of relationship between Knowledge and Efficiency toward Customer Satisfaction. Respondents that involve in this research study are mainly clients of Anika Insurance Brokers Sdn Bhd that having a claim history with Anika with 50 questionnaires were distributed toward them. At the end of this research, researcher found that all of the independent variable is trust to be the important factors that contribute towards customer satisfaction among clients of Anika Insurance Brokers Sdn Bhd.